Uji Daya Hambat Ekstrak Daun Ketapang (Terminalia catappa L.) terhadap Pertumbuhan Bakteri Staphylococcus aureus - Meyke Widyaningrum; Damajanty H. C. Pangemanan; Christy N. Mintjelungan (Universitas Sam Ratulangi, 2026)
Abstract: Staphylococcus aureus belongs to the normal flora in the human body, however, it can become pathogenic when mucosal surfaces are subjected to trauma or abrasion. The ketapang plant (Terminalia catappa L.) contains antibacterial compounds such as flavonoids. This study aimed to identify the inhibitory effect of ketapang leaf extract on the growth of Staphylococcus aureus. The disk diffusion method was used for the antibacterial assay. Ketapang leaf samples were collected from Sindulang 2 area in Manado, macerated for three days, and prepared into extract concentrations of 70%, 80%, 90%, and 100%; each tested in four replications. The Staphylococcus aureus strain used was obtained from the culture collection of the Laboratory of the Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Sam Ratulangi, Manado. The concentrations of 25%, 50%, 75%, and 100% demonstrated antibacterial activity. The highest mean inhibition zone was observed at the 100% concentration with a diameter of 12.46 mm, while the lowest was at 70% with a diameter of 10.63 mm. The results indicate that ketapang leaf extract possesses inhibitory activity against the growth of Staphylococcus aureus, with higher concentrations producing larger zones of inhibition. Keywords: Staphylococcus aureus; ketapang leaves; inhibitory activity Abstrak: Staphylococcus aureus merupakan flora normal di tubuh manusia, tetapi dapat berubah menjadi patogen saat permukaan mukosa terkena trauma atau abrasi. Tanaman daun ketapang (Terminalia catappa L.) memiliki senyawa antibakteri seperti flavonoid. Penelitian ini bertujuan untuk mengidentifikasi kemampuan ekstrak daun ketapang dalam menghambat pertumbuhan bakteri Staphylococcus aureus. Pengujian ini menggunakan metode difusi cakram. Sampel daun ketapang diambil dari daerah Sindulang 2, Manado yang dimaserasi selama tiga hari dan dibuat menjadi konsentrasi 70%, 80%, 90%, dan 100% dengan empat kali pengulangan. Bakteri Staphylococcus aureus yang digunakan merupakan biakan Laboratorium Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA) Universitas Sam Ratulangi Manado. Hasil pengujian konsentrasi 25%, 50%, 75%, dan 100% menunjukkan aktivitas antibakteri. Rerata diameter terbesar terdapat pada konsentrasi 100% dengan nilai 12,46 mm dan rerata terkecil pada konsentrasi 70% dengan nilai 10,63 mm. Simpulan penelitian ini ialah ekstrak daun ketapang memiliki daya hambat terhadap pertumbuhan bakteri Staphylococcus aureus. Semakin tinggi konsentrasi, semakin besar zona hambat yang terbentuk. Kata kunci: Staphylococcus aureus; daun ketapang; daya hambat